Determinants of A-shares Initial Public Offerings Underpricing in China - Su, Haonan (2017)
IPO underpricing is one of major anomalies of China’s new shares issuance. IPO underpricing in China is more severe than other countries in the world. IPO underpricing can influence the sustained and healthy development of the national economy, so figuring out determinants of A-shares IPO underpricing in China is necessary. The method adapted in this paper is testing hypotheses that based on IPO underpricing theories. Some hypotheses with strong Chinese characteristics that rarely tested by previous researchers are also tested in this paper. Using the latest twenty years data of China’s stock market, useful research results are obtained. Twelve factors are tested in the paper. Four variables have been proved that have stable influence directions on the degree of IPO underpricing. They are the time lag between the offering date and the listing date, return on equity, the offering price and the turnover ratio. Given this, actions can be taken to reduce IPO underpricing in China, so that the economy will be healthier.